Experimental Infiltration Tests on Existing Permeable Pavement Surfaces. Issue 1 (7th December 2015) - Cipolla, Sara Simona; Maglionico, Marco; Stojkov, Irena
Abstract : This study describes a field investigation that compares water infiltration rates of eight permeable parking lots located in Rimini City, Italy. In the experiment a single ring infiltrometer test was used to analyze the influence of the surface type, filling material, location in the parking stall, pavement age, and antecedent dry weather days on the infiltration capacity of the pavements. The results show that the permeability values are mostly affected by the position of the ring in the parking lot, filling material, and surface type rather than by the antecedent dry weather time and pavement age. The surface infiltration rate of the eight pavements ranges between a minimum of 123 mm/h (site 6, permeable interlocking concrete paver, 2005) and a maximum of 20 137 mm/h (site 4, concrete grid paver, 2005), exceeding the 97.2 mm/h minimum design infiltration rate required by selected European authorities. The results also show that compaction decreases the infiltration rate. Therefore, the study could be useful in setting the standard test procedure to evaluate the performance of permeable pavements over time in the Mediterranean climate. Abstract : This study describes a field investigation that compares the water infiltration rates of parking lots using a single ring infiltrometer test to analyze the influence of several factors. Experimental evidence suggests that the permeability values are mostly affected by the position of the ring in the parking lot, filling material, and surface type rather than by the antecedent dry weather time and pavement age.